Leucine supplementation and serum amino acids, testosterone, cortisol and growth hormone in male power athletes during training - Mero, A.; Pitkanen, H.; Oja, S. S.; Komi, P. V.; Pontinen, P.; Takala, T. (The Journal of Sports Medicine and Physical Fitness, 1997)
OBJECTIVE: The purpose of the present study was to examine the effects of leucine supplementation on the amino acid and hormone profile during training. EXPERIMENTAL DESIGN: The study was a randomised double-blind cross-over study during 10 weeks of training. SETTING: The study occurred during a sport training period. PARTICIPANTS: Twenty adult male track and field power athletes finished the study. INTERVENTIONS: The subjects were given leucine (50.0 +/- 3.3 mg/ kg body weight per day) or placebo tablets. MEASUREMENTS: The measurements were carried out before, in the middle of, and after 10 weeks. RESULTS: The serum leucine concentration decreased significantly (p < 0.05) in the placebo group, by 20.1% (from 189 +/- 45 to 151 +/- 21 mumol/l) during the first 5 weeks, but not during the second 5 weeks (180 +/- 61 vs 154 +/- 23 mumol/l). When leucine was taken there were no changes in the serum leucine concentration. The total serum amino acid pool decreased significantly (p < 0.01) in all subjects, by 21.2% during the 10-week training period. The decrease occurred mostly during the first 5 weeks. Glutamine decreased (37.1%; p < 0.01) most of the single amino acids. The serum testosterone concentration increased by 20.7% (p < 0.05) and the serum cortisol concentration by 8.0% (p < 0.05) in all subjects during the first 5 weeks. During the second 5 weeks the testosterone concentration decreased by 19.0% (p < 0.001). CONCLUSIONS: The present findings indicate that on a daily protein intake of 1.26 g/kg body weight the serum concentrations of amino acids are lowered considerably and earlier than the decrease in the serum testosterone concentration during the training season in adult male power athletes. The leucine supplementation of 50 mg/kg body weight per day appears to prevent the decrease in the serum leucine concentration during intensive training.